ISOLATION AND CHARACTERIZATION OF YEAST FROM FERMENTED SEMERU ARABICA WINE COFFEE CHERRIES - Vivianinda, Ange Risna; Nurcholis, Mochamad; Sriherfyna, Feronika Heppy; Maligan, Jaya Mahar (Jurnal Pangan dan Agroindustri, 2024)
Wine coffee is fermented coffee cherries with a wine-like flavor and aroma. The purpose of this study was to isolate, characterize ethanol-tolerant and thermotolerant yeast from Semeru Arabica wine coffee cherries and to determine the molecular identification of the selected yeast. In this study, the Semeru Arabica coffee cherries were fermented for 30 days.Yeast isolation was performed on samples collected each week during fermentation. The selected isolates were characterized for macroscopic and microscopic morphology, followed by ethanol and temperature tolerance analysis. The isolate with the most desirable characteristics, designated CW30, grew well at 30ºC but was sensitive to temperatures above 35ºC. The isolate grew well in media containing 5% ethanol but was sensitive to a 10% ethanol concentration. Based on nucleotide sequence analysis, CW30 exhibited 100% similarity with Candida ethanolica isolate 3-1-19.